Electronic cigarette use in relation to changes in smoking status and respiratory symptoms - Linnéa Hedman+; Gustaf Lyytinen+; Helena Backman; Magnus Lundbäck; Caroline Stridsman; Anne Lindberg; Hannu Kankaanranta; Lina Rönnebjerg; Eva Rönmark; Linda Ekerljung (Tobacco Induced Diseases)
Introduction How e-cigarette use relates to changes in smoking status and respiratory symptoms in the population remains controversial. The aim was to study the association between e-cigarette use and, changes in smoking status and changes in respiratory symptoms.